2018
DOI: 10.21776/ub.jam.2018.016.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Marketing Strategy Adaptation on Knowledge Exploitability

Abstract: The objectives of this research is establishing a theoretical model to explain the effect of marketing strategy adaptation on knowledge exploitability. The research is a modeling approach, by using the library and literature method. Besides that, the study employs the theoretical study to strengthen the relationships among the founded concepts.The results of this study are propositions formulated in the form of basic theoretical models and developed in the form of hypotheses and empirical models of research.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…Marketing programs can accommodate differences in environmental and consumer behavior to accommodate the exploit opportunities. The result of this study supports the previous research conducted by Nurcholis (2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Marketing programs can accommodate differences in environmental and consumer behavior to accommodate the exploit opportunities. The result of this study supports the previous research conducted by Nurcholis (2018).…”
Section: Discussionsupporting
confidence: 92%
“…Sharing marketing programs with other business units to increase profit margins to achieve greater efficiency (Bahri-Ammari & Bilgihan, 2017). Marketing program development as the degree of variation of marketing development and expand marketing programs to accommodate differences in environmental and consumer behavior to accommodate the exploit opportunities and capacity to identify more quickly than rivals (Nurcholis, 2018). These programs can affect knowledge (Nejatian et al, 2018), current skills and abilities (Subramony et al, 2018), responsiveness, operational flexibility, and business relationships (Baškarada & Koronios (2018), Worren et al (2014), Teoh & Cai (2015), Doz & Kosonen (2010), Sambamurthy et al (2003), Joshi & Sharma (2004), Conboy (2009).…”
Section: Development Of Marketing Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding showed that new market exploitation, product diversity and marketing program development as measures for adaptive behaviour have significant positive influence towards knowledge exploitability. This finding further explained that ability of firms to adapt and respond to market changes by creating ideas in the market place depends on its ability to analyse and make consistent use of market information culminates into market knowledge to adjust marketing activities that meet new market demands and customers needs (Nurcholis, 2018). Ramaseshan, Ishak, and Kingshott (2013) found that marketing analysis as a dimension of strategic marketing as an important instrumental link between the firm and its external environment helps ascertain how well the firm is able to respond and adapt to environmental constraints and changes in its marketing activities.…”
Section: Discussionmentioning
confidence: 95%
“…A company's ability to analyze situations and determine the direction in implementing new service strategies through a search process for customer needs and desires, market demand, competitor analysis, and intention to develop or produce new methods for creating services (Nurcholis, 2018). Therefore, organizations must adapt and respond to change by improving or creating new ideas to the market to find new opportunities and achieve success.…”
Section: Marketing Adaptation Strategymentioning
confidence: 99%